The Effectiveness Of Methaporical Thinking Approach To Improve The Mathematical Representation Ability - Haidar, Irajuana; Jahring, Jahring (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
This research is an experimental research which aims to describe the effectiveness of the methaporical thinking approach to improve the mathematical representation ability of class VIII SMPN 2 Toari. In addition, it also aims to determine how much students are engaged in the learning process when applying the methaporical thinking approach. The research subjects were divided into two groups, namely the experimental group taught using the methaporical thinking approach and the control group taught by conventional learning. The results showed that students who were taught with a methaporiical thinking approach were more active in the learning process so that the ability of representation also increased. In addition, it was found that mean of mathematical representation ability of students taught using the approach of methaporical thinking was better than students taught with conventional learning. Therefore, the approach of methaporical thinking is able to improve the mathematical representation ability of class VIII SMPN 2 Toari